Leaf-mining by Phyllonorycter blancardella reprograms the host-leaf transcriptome to modulate phytohormones associated with nutrient mobilization and plant defense. (January 2016) - Zhang, Hui; Dugé de Bernonville, Thomas; Body, Mélanie; Glevarec, Gaëlle; Reichelt, Michael; Unsicker, Sybille; Bruneau, Maryline; Renou, Jean-Pierre; Huguet, Elisabeth; Dubreuil, Géraldine; Giron, David
Graphical abstract: Highlights: A comprehensive analysis of phytohormone alterations by a leaf-miner was conducted. A general transcriptomic and biochemical reprogrammation is observed in the mine. Cytokinins accumulate in mined-tissues. Expression of cytokinin-related genes suggest a cytokinin production by the insect. Cytokinins interfere with the global phytohormonal balance. Abstract: Phytohormones have long been hypothesized to play a key role in the interactions between plant-manipulating organisms and their host–plants such as insect–plant interactions that lead to gall or 'green-islands' induction. However, mechanistic understanding of how phytohormones operate in these plant reconfigurations is lacking due to limited information on the molecular and biochemical phytohormonal modulation following attack by plant-manipulating insects. In an attempt to fill this gap, the present study provides an extensive characterization of how the leaf-miner Phyllonorycter blancardella modulates the major phytohormones and the transcriptional activity of plant cells in leaves of Malus domestica . We show here, that cytokinins strongly accumulate in mined tissues despite a weak expression of plant cytokinin-related genes. Leaf-mining is also associated with enhanced biosynthesis of jasmonic acid precursors but not the active form, a weak alteration of the salicylic acid pathway and a clear inhibition of the abscisic acid pathway. Our study consolidates previous results suggesting that insects may produce and deliver cytokinins to the plant as a strategy to manipulate the physiology of the leaf to create a favorable nutritional environment. We also demonstrate that leaf-mining by P. blancardella leads to a strong reprogramming of the plant phytohormonal balance associated with increased nutrient mobilization, inhibition of leaf senescence and mitigation of plant direct and indirect defense.